Lignocellulolytic fungi and their enzymes: biotechnological potential in Cuba - Elaine C.; Maryen; J. C.; Yaneisy; Lourdes L.; Madeleidy (Cuban Journal of Agricultural Science, 2025)
The revaluation of lignocellulosic biomass for use in animal production has been studied as a solution to the food shortage in this sector. This review deals with aspects related to lignocellulolytic fungi, their enzymes, and their biotechnological potential in Cuba. Information is collected on the progress made in bioconversion processes using solid-state fermentation with strains that are highly productive of bioactive compounds. The diversity and versatility of cellulases and ligninases with the ability to degrade complex substrates and phenolic compounds are described. This constitutes an interesting challenge today, which involves elucidating the complex biochemical and physiological mechanisms involved in fungal degradation. The design of strategies for the production of lignocellulolytic enzymes will allow improving digestibility and nutritional quality of alternative sources, which can achieve more efficient agricultural production in a sustainable and ecological way.